2014
DOI: 10.2215/cjn.01340214
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Affect and Hospitalization Risk in Incident Hemodialysis Patients

Abstract: Background and objectives Recent studies demonstrated an association between depressive affect and higher mortality risk in incident hemodialysis patients. This study sought to determine whether an association also exists with hospitalization risk.Design, setting, participants, & measurements All 8776 adult incident hemodialysis patients with Medical Outcomes Study Short Form 36 survey results treated in Fresenius Medical Care North America facilities in 2006 were followed for 1 year from the date of survey, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 41 publications
2
33
1
Order By: Relevance
“…Of the remaining publications, 13,083 were excluded for reasons listed in Figure 1; 106 potentially relevant articles were subsequently screened as full text. Ultimately, 27 full-text publications were considered relevant to our search ( Eight studies focused on hemodialysis (27,28,31,33,(35)(36)(37)(38), and three studies focused on peritoneal dialysis only (24,29,43). Fifteen studies performed the screening for impairments at dialysis initiation, and 12 studies performed the screening for impairments within 3 months after initiation.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the remaining publications, 13,083 were excluded for reasons listed in Figure 1; 106 potentially relevant articles were subsequently screened as full text. Ultimately, 27 full-text publications were considered relevant to our search ( Eight studies focused on hemodialysis (27,28,31,33,(35)(36)(37)(38), and three studies focused on peritoneal dialysis only (24,29,43). Fifteen studies performed the screening for impairments at dialysis initiation, and 12 studies performed the screening for impairments within 3 months after initiation.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Hospitalization days after dialysis initiation were assessed in three studies (Table 3) showing that malnutrition (43), depression (36), and performance status (37,43) were associated with more days in hospital. However, the association between performance status and hospitalization duration was lost after adjustment for potential confounders in one of the two studies (P=0.50) (37).…”
Section: Relation Of Geriatric Impairments and Hospitalizationmentioning
confidence: 99%
See 1 more Smart Citation
“…In a second report focused on depressive affect, Lacson et al (12) retrospectively evaluated 8776 incident adult hemodialysis patients from a large United States cohort. Using the SF-36 survey administered shortly after dialysis inception, they observed that approximately 40% of patients had depressive symptoms and that depression was associated with a higher risk of hospitalization and more hospitalization days during the subsequent 12 months of treatment.…”
mentioning
confidence: 99%
“…If we could aggregate these three studies, we would find that elderly patients with CKD would have higher risk of depressive symptoms (11), depression is associated with more hospitalization when patients start MD (12), and greater physical activity during hemodialysis is associated with better quality of life and fewer depressive symptoms. These finding suggest that physical activity should be enforced in all dialysis facilities.…”
mentioning
confidence: 99%